Bioelectricity Generation in Mediator-less Microbial Fuel Cell: Application of Pure and Mixed Cultures - Sakine Fatemi; Ali Asghar Ghoreyshi; Ghasem D. Najafpour; Mostafa Rahimnejad (Iranica Journal of Energy and Environment, 2012)
Microbial fuel cell (MFC) is an emerging biotechnology, which converts the organic substrates to electricity by electrogenic bacteria. In this study, electricity generation was evaluated in a dual chamber mediator-less microbial fuel cell. Graphite plates were used as electrodes and glucose with initial concentration of 4 g/L was used as electron donor. Anode chamber of the fabricated MFC was inoculated with two mixed cultures; anaerobic effluent of dairy manufacture (called A) and anaerobic effluent of wastewater treatment plant (called B). Saccharomyces cerevisiae PTCC 5269 was used as pure culture. Power generation using these three inoculums was evaluated in the same condition including room temperature, without agitation and using glucose with initial concentration of 4 g/L as substrate. The performance of MFC was analyzed by the measurement of polarization curve. Maximum power and current densities of 30.99 mW/m2 and 391.68 mA/m2; 25.90 mW/m2 and 320.7604 mA/m2 were obtained when culture B and A were used as inoculums, respectively. Power and current densities were 10.0224 mW/m2 and 253.2964 mA/m2 when S. cerevisiae was used as pure culture in MFC. Therewith, chemical oxygen demand (COD) removal efficiencies of 54, 71 and 75% were achieved when S. cerevisiae, mix cultures A and B were used as inoculums, respectively. The investigation was targeted for the capability of mediator-less microbial fuel cell as combined wastewater treatment and electricity production unit.